2016
DOI: 10.1155/2016/8169614
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Altered Canonical Wnt Signaling in the Trabecular Bone of Elderly Postmenopausal Women with Fragility Femoral Fracture

Abstract: Wnt signaling, a major regulator of bone formation and homeostasis, might be involved in the bone loss of osteoporotic patients and the consequent impaired response to fracture. Therefore we analyzed Wnt-related, osteogenic, and adipogenic genes in bone tissue of elderly postmenopausal women undergoing hip replacement for either femoral fracture or osteoarthritis. Bone specimens derived from the intertrochanteric region of the femurs of 25 women with fracture (F) and 29 with osteoarthritis without fracture (OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Wnt pathway is a critical regulator of bone formation, thus its disequilibrium could be involved in bone loss and consequent fracture events in OP patients. Bolamperti et al [ 69 ] first analyzed the expression of genes involved in Wnt signaling, osteogenesis and adipogenesis processes in bone tissues derived from 25 women with femoral neck fracture and 29 nonfractured osteoarthritic patients (OA). The results showed a decrease in the expression of genes associated with osteogenesis in the fractured group compared to the OA group.…”
Section: Circulating Mirnas As Potential Biomarkers In Bone Fragilmentioning
confidence: 99%
“…Wnt pathway is a critical regulator of bone formation, thus its disequilibrium could be involved in bone loss and consequent fracture events in OP patients. Bolamperti et al [ 69 ] first analyzed the expression of genes involved in Wnt signaling, osteogenesis and adipogenesis processes in bone tissues derived from 25 women with femoral neck fracture and 29 nonfractured osteoarthritic patients (OA). The results showed a decrease in the expression of genes associated with osteogenesis in the fractured group compared to the OA group.…”
Section: Circulating Mirnas As Potential Biomarkers In Bone Fragilmentioning
confidence: 99%
“…In the study of Bolamperti et al [ 23 ], both groups had comparable BMD. The expression of the WNT pathway activators: WNT3 and WNT10B , was comparable in both groups, similarly as the CTNNB1 , which was consistent with our results.…”
Section: Discussionmentioning
confidence: 98%
“…The use of HRT, reported by almost a half of the participants, could have been responsible for the differences in DKK1 expression versus our results. Bolamperti et al [ 23 ] compared Wnt pathway gene expression in bone samples, collected from patients with osteoporosis and/or osteoarthrosis (OA) that were qualified to hip arthroplasty. Similarly, as in our investigation, the expression of CTNNB1 was in both groups decreased, however, differently than in our experiment, the DKK1 expression was comparable to the reference gene.…”
Section: Discussionmentioning
confidence: 99%
“…The various studies often have different designs and purposes, and therefore are not directly comparable. Sclerostin is a central inhibitor of the Wnt signaling pathway, and various parts of the Wnt signaling system have been associated with bone status in most types of -omics analyses including GWAS, e.g., β-Catenin and DKK1 in proteomics ( 187 ); SOST, DKK1, WIF1, CTNNB1, and WNT5B in transcriptomics ( 193 , 196 ); FZD10, TBL1X, CSNK1E, WNT8A, CSNK1A1L, SFRP4, and SOST in DNA methylation studies ( 221 , 223 ). Also, TGF-β signaling genes ( 187 , 196 , 198 ) and regulators of osteoclast function ( 187 , 197 , 199 , 242 ) have been identified in more than one type of -omics analysis.…”
Section: Overview Of –Omics Data Resources From Human Bone Tissuementioning
confidence: 99%
“…Sclerostin is a central inhibitor of the Wnt signaling pathway, and various parts of the Wnt signaling system have been associated with bone status in most types of -omics analyses including GWAS, e.g., β-Catenin and DKK1 in proteomics ( 187 ); SOST, DKK1, WIF1, CTNNB1, and WNT5B in transcriptomics ( 193 , 196 ); FZD10, TBL1X, CSNK1E, WNT8A, CSNK1A1L, SFRP4, and SOST in DNA methylation studies ( 221 , 223 ). Also, TGF-β signaling genes ( 187 , 196 , 198 ) and regulators of osteoclast function ( 187 , 197 , 199 , 242 ) have been identified in more than one type of -omics analysis. Furthermore, a study of DNaseI hypersensitive sites during osteoblast differentiation identified changes in chromatin and expression of several genes within the Wnt and TGF-β signaling pathways ( 232 ).…”
Section: Overview Of –Omics Data Resources From Human Bone Tissuementioning
confidence: 99%